Analisis Kinerja Routing Dinamis Dengan Teknik Open Shortest Path Frist Pada Topologi Mesh Dalam Jaringan LAN Menggunakan Cisco Packet Tracer - Husni Mubarok; H.Jazuli Mukhtar (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
A computer network that has a few clients will make the data path less complicated. This condition will minimize the occurrence of route collisions, but if the conditions are different, namely in the mesh topology or on other network segments. All devices/nodes in a network are connected to each other so that the exchange of data will affect the quality of the network connection. Because the need for computer network information is very important, especially to detect network failures quickly, easily and cheaply, to overcome the above problems, network administrators need a network monitoring system application for simulation that can reflect the computer network architecture on the network that is being used. By using the Cisco Packet Tracer application, simulation data on the network can be used as information about the connection status of computers on the network in case of network connectivity problems. local area network built with Cisco Packet Tracer software, which when tried to successfully connect over a wireless network. Testing whether the server-to-client or client-to-server connection has been successfully carried out.